Functional characterisation of transcription factors with potential as key regulators of palm oil production - Chin, Mei Yee (2016)
Transcription factors play important and diverse roles in regulating gene expression. Each transcription factor binds to a specific DNA sequence (cis-elements) in the promoter region and can either activate or suppress the downstream gene expression. They have been known to coordinate expression of genes involved in the same biosynthetic pathway or physiological process. Three transcription factors EgNFYB3,EgLEC2 and EgWRI1-ANT were the target for studying transcriptional regulation of fatty acid biosynthesis in the oil palm. The sequences of the open reading frame were verified based on homology with known transcription factor sequences from other plant species. Recombinant vector constructs, each harbouring one of the selected transcription factors were constructed via Gateway cloning system. The oil palm genes driven by the cauliflower mosaic virus 35S constitutive promoter were introduced separately into 12 WAA (weeks after anthesis) oil palm mesocarp tissue slices, which is the period preceding oil synthesis through particle bombardment system. Each one was co-bombarded with a green fluorescent protein (GFP) reporter vector. Mesocarp tissue slices which expressed GFP protein at 48 hours post-bombardment were selected for total RNA extraction. High throughput sequencing (RNA-Seq) and transcript profiling of transiently transformed mesocarp slices were performed to determine genes whose expression is affected by transient over-expression of each transcription factor. RNA-Seq results were analysed for differentially expressed genes that are involved in fatty acid biosynthesis, glycolysis and TAG assembly pathways. EgNFYB3 bombarded tissues upregulated transcripts encoding enzymes for glycolysis, EgWRI1-ANT bombarded tissues upregulated transcripts encoding enzymes in fatty acid biosynthesis and glycolysis, while EgLEC2 bombarded tissues upregulated a transcript encoding an enzyme from fatty acid biosynthesis pathway in both biological replicates. RT-qPCR validation of the differentially expressed genes were performed and the results showed correlation to the RNA-Seq data. EgWRI1-ANT was chosen for subsequent DNA-protein interaction in vivo with yeast one-hybrid assay and EMSA for in vitro study. RNA-Seq results reveal the role of EgWRI1-ANT transcription factor in regulating genes related to glycolysis and fatty acid biosynthesis. Yeast one-hybrid assay confirmed that EgWRI1-ANT transcription factor binds to the AW-box 1cis-element to activate transcription of the genes it upregulated. These results demonstrate that oil palm transcription factors EgNFYB3, EgLEC2 and EgWRI1-ANT are important transcriptional regulator of carbohydrate metabolism and fatty acid biosynthesis in oil palm mesocarp, a non-seed oil-rich tissue, thus making them candidates for future development of molecular tools for genetic improvement of the oil palm.